The Effect of Cooperative Learning Model Type Team-Games-Tournament on Improving Basketball Game Learning Outcome - Masayu Rizka Risjanna; Lukmannul Haqim Lubay; Patriana Nurmansyah Awwaludin (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
The purpose of this study was to see the effect of the cooperative learning model for improving the basketball game learning outcomes. The method used was experimental research. The population of the study were the students who joined basketball extracurricular activities at a State High School in Bandung. The samples were 15 female students divided into 3 playgroups. The one-group pre-test-post-test research design was used. The Game Performance Assessment Instrument was used as the instrument to collect data. To process and to analyse the obtained data, paired t-test was employed. Based on the results of these calculations, it concludes that the cooperative learning model type team-games-tournament have a significant effect on improving the basketball game learning outcomes of the students who take part in basketball extracurricular activities.